ANALISIS KETIDAKSETABILAN HARGA DAGING DI PASAR TRADISIONAL KAJEN - monica nour fauziah (Sahmiyya, 2022)
This study aims to analyze the instability of beef prices in the Kajen traditional market, from producers to final consumers. This study uses a survey method with respondent units selling beef in the Kajen market and descriptive quantitative methods, using secondary data analysis. The object of this research is beef traders which includes data on beef cattle production, beef production, domestic retail beef prices, international beef prices, beef import volume, factors that affect retail prices. The population in this study were 7 traders in the Kajen traditional market. Samples were taken by quota sampling method. The results showed that the instability of meat prices was influenced by the demand and supply factors of the meat itself, the sale of meat which usually consumes 15 kilograms per day is now only 10 kilograms. Now, the price of beef has reached Rp. 110 thousand per kilogram, which previously cost 105,000 per kilogram of beef. The increase is influenced by the plan to be subject to a sales tax of 10 percent.